Associations between MDMA/ecstasy use and physical health in a U.S. population-based survey sample. (October 2022) - Jones, Grant; Ricard, Jocelyn A.; Hendricks, Peter; Simonsson, Otto
Introduction: 3, 4-Methylenedioxymethamphetamine (MDMA/"ecstasy") is an empathogen that can give rise to increased pleasure and empathy and may effectively treat post-traumatic stress disorder. Although prior research has demonstrated associations between ecstasy use and favorable mental health outcomes, the associations between ecstasy and physical health have largely been unexplored. Thus, the goal of this study was to examine the associations between ecstasy use and physical health in a population-based survey sample. Method: This study utilized data from the National Survey on Drug Use and Health (2005–2018), a yearly survey that collects information on substance use and health outcomes in a nationally representative sample of U.S. adults. We used multinomial, ordered, and logistic regression models to test the associations between lifetime ecstasy use and various markers of physical health (self-reported body mass index, overall health, past year heart condition and/or cancer, past year heart disease, past year hypertension, and past year diabetes), controlling for a range of potential confounders. Results: Lifetime ecstasy use was associated with significantly lower risk of self-reported overweightness and obesity (adjusted relative risk ratio range: 0.55–0.88) and lower odds of self-reported past year heart condition and/or cancer (adjusted odds ratio (aOR): 0.67), hypertension (aOR: 0.85), and diabetes (aOR: 0.58). Ecstasy use was also associated with significantly higher odds of better self-reported overall health (aOR: 1.18). Conclusion: Ecstasy shares protective associations with various physical health markers. Future longitudinal studies and clinical trials are needed to more rigorously test these associations.